Contribution to the early diagnosis of prostate carcinoma - González Villalobos, Rodolfo (1947)
This paper entitled "Contribution to the early diagnosis of prostate carcinoma", is the first work in Peru, on the clinical role of acids enzimos blood serum in the early diagnosis of prostate cancer.